A Rare and Dangerous Complication of Central Venous Catheterization: Intimal Injury - Emine Akkuzu; Gökhan Kalkan; Ece Geylan Durgun; Abdullah Özer (Galenos Yayinevi, 2017)
Central venous catheters are frequently used for urgent patient resuscitation and for prolonged intravenous route requirements. However, the patient may be injured or may need additional intervention due to complications associated with catheter insertion. Various mechanical complications such as catheter malposition, arterial puncture, hemothorax and pneumothorax can be seen in 5-19% of patients and early recognition has a vital effect. Here, we present a case of pleural effusion leading to significant hypoxemia due to intimal injury to the superior vena cava which developed in the second day of catheter insertion.